Influences of Social Media on Omani Youth’s Health - Muthuraman, Subrahmanian (Journal of Ecohumanism, 2024)
The study focused on the influences of social media on Omani Youth and their lifestyle. The challenges associated with social media may be especially risky for young people who are already experiencing mental health difficulties, as suggested by the bidirectional relationship between the use of electronic media and a decrease in psychological well-being. Social media causes depression and anxiety from stress. Depression and emotional instability are some of the main psychological problems shown in many youths. There is a need for public awareness campaigns and social policy initiatives that promote nurturing home and school environments that foster resilience as youth navigate the challenges of adolescence in today’s world. The youth should avoid excessive use of social media. They should be balanced in their life and give proper time to other activities that will help them to develop their capabilities.